That time cannot be forgotten : a correspondence on the Holocaust - Sold, Emil Georg (Indiana University Press, 2002)
In a gripping exchange of letters written in the closing years of the 20th century, two men struggle to come to terms with the signal event of their time, the Holocaust. Born in the Rhineland-Palatinate region of Germany in the early part of the 20th century, both bore witness to the turbulent years of the Weimar Republic, Hitler, World War II, and the Holocaust. But their perspectives were entirely different. Emil Sold was a Catholic who served in the Wehrmacht during World War II. Paul Friedhoff, a Jew.